Improving Number Symbol Recognition Through Concrete Objects in Hearing-Impaired Elementary Students at State Special Schools A, B, and D, Kedungkandang - Anggraini, Adelia Ayu; Yuniar, Hana Fitri (Proceedings Series of Educational Studies, 2024)
This study aims to determine the improvement of the ability to recognize number symbols through concrete objects media in Deaf elementary school students at SLB A,B,D Negeri Kedungkandang The research method used is class action research with the use of concrete media. Based on the results of the study, it is stated that concrete media using decorative stones can be used to improve the ability to recognize number symbols in deaf children in SLB A,B,D Negeri Kedungkandang. This is evidenced by an increase in the learning outcomes test of the ability to recognize number symbols.